Readiness mainstream primary school to cater for children with disabilities (CWDS) in Bangladesh in line with universal design (UD) - Hossain, Md. Zaman; Abdul Rahim, Asiah (2015)
The objectives of this paper firstly, to explore the level of accessibility for Children with Disabilities (CwDs) in mainstream school environment in Bangladesh. Secondly, to study the level of perception of players in building industry in application of Universal Design for (CwDs) in school built environment. There is little awareness among the decision makers, professionals in the building industry on providing good facilities for People with Disabilities (PwDs) who are the children of the school. Table research will be used on literature review and using secondary data. In conclusion, rule and guidelines on facilities for CwDs in primary school buildings will be produced.